Laparoscopic choledochal cyst excision and Roux-en-Y hepaticojejunostomy in children: a single-institution prospective cohort study - Xuan, Nguyen Thanh; Thien, Ho Huu; Thanh, Phan Hai; Vu, Pham Anh; Son, Nguyen Huu; Thanh, Dang Nhu; Vinh, Nguyen Du; Hiep, Pham Nhu (International Surgery Journal, 2019)
Background: Laparoscopic cyst excision and Roux-en-Y hepaticojejunostomy is gaining popularity as a treatment for choledochal cyst in children. The aim of this study is to determine the feasible and safe of the laparoscopic excision with Roux-en-Y hepaticojejunostomy, and evaluate the short-term outcomes after treatment for children with choledochal cyst. Methods: A prospectively of 51 consecutive pediatric patients undergoing laparoscopic choledochal cyst excision and Roux-en-Y hepaticojejunostomy performed by one surgeon cysts at Hue Central Hospital from June 2012 to December 2017 was studied. Results: The mean operative time was 214.7±67.95 minutes (range, 100 360 minutes), including the time for intraoperative cholangiography. There were two children requiring blood transfusion. Time to first flatus was 40.35±28.55 hours in average. The mean time to drain removal was 2.89±1.02 days. Mean postoperative hospital stay was 9.31±3.43 days. 6 out of 51 cases having early complications, including 2 cases of pancreatitis and 4 cases of bile leakage. Most of cases (90.5%) were classified as good after 10 days to 3 months of follow-up. Conclusions: Laparoscopic choledochal cyst excision and Roux-en-Y hepaticojejunostomy was feasible and safe in children. The short-term outcomes were good in most cases.